From Need to Action: Developing an E-Module for Teaching Arabic Rhetoric (Ilm al-Bayan) through the CLIL Approach - Meliza Budiarti; Mohammad taufiq Abdul Ghani (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Arabic Rhetoric (Ilm al-Bayan) is often perceived as challenging by university students due to its abstract concepts and reliance on traditional, teacher-centered instruction. Despite its linguistic and cultural importance, efforts to modernize its teaching through pedagogically sound, technology-enhanced methods remain limited. This study addresses this gap by integrating the ADDIE instructional design model with the Content and Language Integrated Learning (CLIL) approach to develop an interactive e-module tailored specifically for Ilm al-Bayan instruction. Employing a quasi-experimental design, the research involved 110 undergraduate students from the Arabic Language Department at State Islamic University in Padang. Data collected through expert validation, questionnaires, pre-tests, and post-tests were analyzed both statistically and thematically. The findings reveal that while students acknowledge the value of Ilm al-Bayan for developing linguistic, aesthetic, and critical skills, they face significant challenges due to outdated resources, teacher-centered approaches, and limited interactivity. Students expressed a strong preference for flexible, autonomous, and interactive learning tools, particularly digital platforms. Results demonstrate that the CLIL-based e-module effectively addresses these needs by combining meaningful content with language learning through multimedia, interactive exercises, and instant feedback, thereby enhancing comprehension, motivation, and self-directed learning. This need analysis confirms the timeliness and necessity of developing a CLIL-integrated e-module for Ilm al-Bayan, offering a transformative approach that makes Arabic Rhetoric education more engaging, accessible, and effective in higher education contexts.